1989
DOI: 10.1203/00006450-198906000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Chemokinetic Agents for Monocytes in Human Milk: Possible Role of Tumor Necrosis Factor-α

Abstract: ABSTRACT. Human milk was found to contain chemokinetic agents for human blood monocytes. The chemokinetic agents were whey proteins that were inactivated by heating at 56" C for 20 min or treatment with trypsin. Three peaks of chemokinetic activity less than 60 kD in size were found by gel filtration chromatography. The chemokinetic activity of each peak obtained by gel filtration was partially blocked by polyclonal rabbit antibodies to recombinant human tumor necrosis factor-a (TNF-a). TNF-a, or a protein tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…These factors proved to be proteins whose approximate M r as determined by gel filtration were 50-60, 25, and 10-17 kDa 1311. The chemokinetic activities in HM were partially blocked by polyclonal antibodies to human recombinant tumor necrosis factor-a (TNF-a) [31]. Since then, we have found immunochemical evidence for TNF-a in HM 1361.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…These factors proved to be proteins whose approximate M r as determined by gel filtration were 50-60, 25, and 10-17 kDa 1311. The chemokinetic activities in HM were partially blocked by polyclonal antibodies to human recombinant tumor necrosis factor-a (TNF-a) [31]. Since then, we have found immunochemical evidence for TNF-a in HM 1361.…”
mentioning
confidence: 78%
“…Recently we reported that chemokinetic agents for monocytes are present in HM and that the increased motility of HM macrophages may be due to these agents [31]. These factors proved to be proteins whose approximate M r as determined by gel filtration were 50-60, 25, and 10-17 kDa 1311.…”
mentioning
confidence: 99%
“…When blood mononuclear cells were incubated in whole human colostrum or its whey protein fraction, the motility of the blood monocytes increased to that of milk macrophages (8). The activity was abrogated by trypsin and considerably decreased by polyclonal antibodies to rhTNFa.…”
mentioning
confidence: 98%
“…The RNA was denatured in a loading buffer containing Sephacryl S-200 gel filtration column (Pharmacia LKB Biotech-formamide and formaldehyde. The concentration of RNA was nology, Piscataway, NJ) (8). The resultant fractions were concen-estimated spectrophotometrically at 260 nm.…”
Section: Subject Selection This Study Was Approved By the Institutionalmentioning
confidence: 99%
See 1 more Smart Citation